2021
DOI: 10.1186/s12974-021-02103-4
|View full text |Cite
|
Sign up to set email alerts
|

Systemic administration of β-glucan induces immune training in microglia

Abstract: Background An innate immune memory response can manifest in two ways: immune training and immune tolerance, which refers to an enhanced or suppressed immune response to a second challenge, respectively. Exposing monocytes to moderate-to-high amounts of bacterial lipopolysaccharide (LPS) induces immune tolerance, whereas fungal β-glucan (BG) induces immune training. In microglia, it has been shown that different LPS inocula in vivo can induce either immune training or tolerance. Few studies focu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…In a mouse model of Alzheimer’s disease, trained immunity exacerbated the disease while tolerance alleviated it. A recent study confirmed the finding of LPS-induced training and demonstrated that systemic β-glucan administration could also induce trained immunity in microglia [ 296 ]. However, the trained phenotype of microglia was only observed two days after the priming and was no longer present at day 7, possibly indicating a lack of sustained epigenetic reprogramming.…”
Section: Aging As a Multisystem Maladysupporting
confidence: 58%
“…In a mouse model of Alzheimer’s disease, trained immunity exacerbated the disease while tolerance alleviated it. A recent study confirmed the finding of LPS-induced training and demonstrated that systemic β-glucan administration could also induce trained immunity in microglia [ 296 ]. However, the trained phenotype of microglia was only observed two days after the priming and was no longer present at day 7, possibly indicating a lack of sustained epigenetic reprogramming.…”
Section: Aging As a Multisystem Maladysupporting
confidence: 58%
“…Although elevated serum BG in DSS mice with oral glucans might be partly due to gut translocation of the administered glucans, there is technical difficulty in the identification of different BGs in blood samples. Then, the inflammatory impact of different forms of BGs was tested by direct injection in mice, and the BGs alone did not induce inflammation [ 74 , 75 , 76 ]. The injection of BG plus LPS enhanced serum cytokine elicitation (TNF-α and IL-6), with the highest potency observed with LPS combined with Pachyman, followed by LPS + WGP [ 10 ], while LPS + Oat-BG only elevated liver IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the administration of beta glucan [ 174 ] and the Bacillus Calmette–Guérin (BCG) vaccine, known as the tuberculosis vaccine, represent the main stimuli able to induce the trained immunity. In particular, the BCG vaccine is considered to be crucial for defense against secondary infections [ 175 , 176 , 177 ].…”
Section: A New Immunity Component: Trained Immunity What Is Its Role In Autoinflammatory Diseases and Cytokine Storms?mentioning
confidence: 99%